Cross-Curriculum Teaching - Georgiev, Yavor (Journal of Education and Vocational Research, 2013)
This article presents the Interdisciplinary collaboration and its potential and value for the modern education process. It also shares several examples from author’s experience in Teaching Foreign Languages and further conclusions about cross-disciplinary work. Future is hold by those who are prepared to work in team and to create new products putting together knowledge from different scientific fields. This approach is one of the major challenges for the educators today, and itÂ´s a fundamental step in the process of creation of future leaders. A few years ago the author got a chance to meet a famous scientist and explorer who hasopened his eyes towards this approach with several examples of collaborative work. Before that, the Interdisciplinary teaching, its potential and value for the contemporary education were no menÂ´s land for the author.Since then, he has been keeping his eyes open to everything surrounding his lifeand he has tracked a good amount of examples of cross-disciplinary work. Now he realizes this is one of the major challenges for the educators today, and itÂ´s a fundamental step in the process of creation of future leaders which weÂ´re attempting to develop.